Disability And Home-School Relations In Cyprus: Hope And Deception - Damianidou, Eleni; Phtiaka, Helen (International Journal about Parents in Education, 2023)
Based on the view that parental participation in the educational process enhances learning, school success and children prosperity, we conducted a preliminary exploratory research, so as to examine the current home-school relations in Cyprus regarding parents with disabled children. Data was collected from semi-structured interviews with six parents of disabled children. The interviewees revealed some gloomy aspects regarding the implementation of the special education law in Cyprus. In particular, the six parents reported that disabled children in Cyprus are often considered incapable of learning and unable to approach the prevalent normality. Such views seem to reflect the prevalence of prejudice and negative stereotypes, which often define home-school relations and teachers’ expectations from disabled children in Cyprus. Secondly, the six parents discussed some segregation education practices, related to unequal power relations, which seem to hinder inclusion. In particular the parents referred to occasional verdicts against the parents’ wishes, which, according to them, were harmful for their disabled children. Thirdly, the interviewees described their feelings regarding home-school relations. In general, the six parents confirmed that ineffective communication, teachers’ attitudes towards disability and problematic home-school relations debar partnership working and result in the exclusion of disabled children.